Characteristics and Functions of Different Intestinal Segments in Juvenile Greater Amberjack (Seriola dumerili) - Kunfeng Zhu; Mouyan Jiang; Mengyao Yan; Yang Huang; Tonglin Yang; Chunhua Zhu (Animals)
The greater amberjack (Seriola dumerili), a key species in marine aquaculture, relies heavily on its intestine for nutrient absorption and immune function. However, the structural and functional specialization of its intestinal segments remains poorly understood. In this study, we divided the intestine of S. dumerili into foregut, midgut, and hindgut, and conducted a multi-omics analysis integrating histological staining (H&E/AB-PAS), digestive enzyme assays, transcriptome sequencing, and 16S rRNA microbiota profiling to characterize structural, functional, molecular, and microbial differences across intestinal segments. Histological examinations revealed that brush border microvillus length, muscle layer thickness, and folding height were significantly greater in the foregut and hindgut compared to the midgut, while mucus and goblet cell density was higher in the foregut and midgut. Digestive enzyme assays showed that lipase activity peaked in the foregut, α-amylase in the midgut, and protease in the midgut and hindgut. Alkaline phosphatase (AKP) and acid phosphatase (ACP) activities were highest in the foregut and midgut. Immune-related enzyme activities (SOD (Superoxide dismutase), GSH-Px (Glutathione peroxidase), T-AOC (Total Antioxidant Capacity)) were elevated and MDA levels were lower in the midgut, indicating its role as the primary immune site. Transcriptome analysis identified segment-specific expression of nutrient transporters, such as slc6a19b (hindgut, protein), apoa1b (foregut, lipid), and slc37a4 (midgut, carbohydrate). Microbiome analysis revealed Ruminococcus dominance in the foregut (lipid digestion) and Prevotella, Bifidobacterium, and Lactobacillus enrichment in the midgut (carbohydrate metabolism and immunity). These findings highlight functional zonation in S. dumerili: the foregut specializes in lipid digestion, the midgut in carbohydrate metabolism and immunity, and the hindgut in protein digestion. This study provides foundational insights for optimizing aquaculture practices and advancing research in nutrition, immunology, and disease modeling in S. dumerili.